Analysis of Crossword Puzzle Therapy to Control Auditory Hallucinations in Sensory Perception Disorder Patients - Jihan Nabilah Yusuf; Arief Budiman; Dwi Rahmah Fitriani; Linda Dwi Novial (CV. CENDIKIA JENIUS INDONESIA, 2026)
Auditory hallucinations are one of the most common and disruptive symptoms experienced by individuals with schizophrenia, often impairing concentration, emotional regulation, and daily functioning. Non-pharmacological interventions, such as cognitive distraction techniques, are increasingly needed to complement medication in managing these symptoms. This study aimed to analyze the effectiveness of crossword puzzle distraction therapy in improving the ability of patients to control auditory hallucinations. A case study design was used involving one patient diagnosed with schizophrenia who received crossword puzzle therapy for three consecutive days. Data were collected through observation, interviews, and the Auditory Hallucination Rating Scale (AHRS), and analyzed descriptively to assess changes before and after the intervention. The patient showed a marked reduction in hallucination intensity, improved focus, and increased ability to redirect attention away from hallucinatory voices. AHRS scores decreased significantly from severe to mild levels, accompanied by behavioral improvements such as calmness, cooperation, and self-control. These findings suggest that crossword puzzle distraction therapy can serve as a practical and effective non-pharmacological strategy in psychiatric nursing care. The study recommends the integration of cognitive activity-based distraction techniques into routine nursing interventions for patients experiencing auditory hallucinations.